Technical-tactical performance in basketball: evaluation of gaming actions according to specific positions - Allan Abou Hatem; Alexandra Folle; Larissa Fernanda Porto Maciel; Raquel Krapp do Nascimento; William das Neves Salles; Juarez Vieira do Nascimento (Motriz: Revista de Educacao Fisica, 2020)
Abstract Aim: This study aimed to analyze the level of technical-tactical performance of female basketball base players, considering the association between the game actions and the specific positions performed by the players. Methods: Twenty-six players from a basketball club in the state of Santa Catarina (Brazil) participated. The performance was analyzed with the aid of the Individual Technical-Tactical Basketball Performance Assessment Instrument (IAD-BB). The statistical treatment involved the use of descriptive (simple and percentage frequency) and inferential (Pearson’s Chi-square test, Cramer’s V coefficients, adjusted residuals), adopting a 5% significance level for the interpretation of the results. Results: It was found a statistically significant association of the functions performed by the players with the actions of reception, dribble, throw, marking and rebound block. The guards performed better in the reception, dribble and clearing actions, the centers were better in rebound block, throw and clearing, while the forwards showed better performance in clearing and rebound block. Conclusion: It is concluded that the analysis of tactical-technical performance, considering the actions and specific positions of female players, is necessary for a better understanding of the factors that influence their performance in the game. Results are discussed with the literature and suggestions are made for future research in order to expand the quantity and quality of evidence in sports performance analysis.